Perubahan Keberagamaan Klien Pasca Terapi Psikospiritual Islam - Endah Wahidah; Rifki Rosyad; Ilim Abdul Halim (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to identify and analyze: (1) the description of the client's religious condition before Islamic Psychospiritual therapy, (2) the process of Islamic Psychospiritual therapy conducted at the Living Meaning Center Foundation Bandung; (3) The client's religiosity after Islamic Psychospiritual therapy; (4) Changes in the client's religiosity after Islamic Psychospiritual therapy. This study uses a qualitative method with a descriptive-analytic approach, the primary source in this study is to clients after Islamic Psychospiritual therapy at the Yayasan Living Meaning Center Bandung. The results of this study indicate that: (1) The client's religious description before Islamic Psychospiritual therapy exists. (2) The process of Islamic psychospiritual therapy at the Bandung Living Meaning Center foundation is carried out with an early-stage counseling procedure. (3) There is a change in the client's religiosity after Islamic psycho-ritual therapy—religious changes in clients after Islamic Psychospiritual therapy at the Living Meaning Center Foundation in Bandung. In the appreciation dimension, most clients become calmer and live more meaningfully. In the consequence dimension, the client becomes more grateful in living his life so that life is more concerned with fellow human beings as humans must become khalifah fil ardhi.